Occurrence and dissipation of antibiotics in manure-amended vegetable greenhouse soils under sprinkling irrigation - Kaifeng Yang; Fangkai Zhao; Lei Yang; Yong Huang; Linjun Shen; Honglin Liu; Qingyu Feng; Liding Chen (Environmental Research Communications)
Agricultural practices critically influence the dissipation of antibiotics in soil, particularly in intensive vegetable greenhouses. This study examines how manure fertilization and irrigation techniques affect antibiotic behavior to improve management practices and reduce contamination. Soil samples were collected from plastic greenhouses with different fertilization periods (0, 5, and 10 years). Regression models were employed to quantify the relationships and interactions among agricultural management intensities, soil characteristics, and antibiotic dissipation. In soils with a long history of organic fertilization, significantly higher antibiotic residues were observed compared to those with less or no fertilization. The concentration of antibiotics decreased further away from irrigation sources, suggesting that irrigation patterns significantly affect their spatial distribution ( R ^2 ≥ 0.90, p ≤ 0.05). Prolonged fertilization increased soil pH and organic carbon, which impeded antibiotic dissipation, whereas enhanced soil moisture actively facilitated it ( λ = 0.48, p < 0.001). These findings underscore the profound impact of agricultural practices on antibiotic dissipation, advocating for adjustments in these practices to mitigate antibiotic contamination and bolster agroecosystem sustainability. The insights provided are crucial for developing targeted strategies to minimize antibiotic residues in agricultural soils, ultimately supporting healthier and more sustainable farming environments.